Nilai Tukar Subsisten Dan Kesejahteraan Petani Kelapa di Desa Teluk Ketapang Kecamatan Senyerang Kabupaten Tanjung Jabung Barat - Nida Kemala; Kholik Maulana (Universitas Batangahari Jambi, 2023)
This study was carried out in Teluk Ketapang Village, Senyerang District, Tanjung Jabung Barat. It used a survey method which the number of samples taken were 37 farmers. The aimed of this reseach were to describe the coconut farming, to analyze the subsistence exchange rate of the and to know the welfare of coconut. This study informed that the planting was done of 9x9x9 meters as a distance . Farmers applied fertilization (NPK and Urea) and sprayed with herbicides ( gramaxone and round-up), The collecting coconut products were sold to middlemens. The Subsistence Exchange Rate was 0.70 (0.70 < 1), and it means that the revenue of coconut farming was not enough to meet the total expenditure costs of the farmers (both for input of coconut farming and consumtion expenditure). So it can be classified as unwelfare.